(untitled) (The Peerian Journal, 2023)
In this state, the use and application of cloud technology in the educational process, the problems of its use, and the significance of the use of cloud technology in the educational process are analyzed in Uzbekistan. Izucheno, chto ispolzovanie oblachnyx tekhnologiy v obrazovatelnom protsese pozvolyaet ispolzovat bolee shirokiy spectr form i metodov, yavlyaetsya odnim iz sovremennyx sposobov prostit i oblegchit process obuchenia.